Lingkungan Main Bagi Toddler di Dalam Keluarga - Fidesrinur Fidesrinur; Eva Riza; Nurfadilah Nurfadilah (Universitas Al Azhar Indonesia, 2023)
The environment is an important element in the period of early childhood, a sensitive period where children are ready to respond to all stimuli from the environment. The play environment is a very meaningful resource for facilitating children's play activities. This study aims to determine the playing tools used by toddlers, either locomotor, nonlocomotor, and manipulative, and to identify aspects that are generally stimulated by families at toddler age. This study used a qualitative descriptive method with 106 families in Jabodetabek as respondents and the research lasted for 9 months, June 2019- January 2020. The data collection tool used was questionnaire to gather information about the respondent family environment. The data is then processed and analyzed using: (a)Descriptive Statistical Analysis: questionnaire filled by respondents are analyzed for data trends, and (b)Qualitative Analysis: results of descriptive statistical analysis are explained qualitatively through the description of observations and interviews on respondents. The results showed that: 66.04 % toddlers live in nuclear families and 33.96% within extended families. Facilitation from the play environment for toddlers to strengthen the feelings of self, independent activity, and cooperation is quite high, but the possibility for toddlers to play fantasy is quite low. Aspects of development generally stimulated by families at toddler age are more nonlocomotor, and acceleration of technological development in developing children's play has widened the gap on children's playing experiences in familiesKeywords - Toddler, Play environment, Family.